Analisis Efektivitas Pembayaran Zakat Online pada Lembaga Dompet Dhuafa Waspada Kota Medan - Siti Aisa; Fauzi Arif Lubis; Juliana Nasution3 (Masyarakat Ekonomi Syariah Bogor, 2023)
This research aims to find out the online zakat payment system and the effectiveness of online zakat payments in Dompet Dhuafa Waspada. It was conducted at the Dompet Dhuafa Waspada Institute, Medan Regency. The research approach used descriptive cauldrons. The data collection method were in-depth interview, documentation and literature tracing in accordance with the issues discussed.The results concluded that online zakat payments in Dompet Dhuafa Waspada could not be said to be effective. This can be seen in 2020 Dompet Dhuafa Waspada targets the collection of zakat funds which was around 4.3 Billion or called Realistic Target while the funds collected in that year only reached 4.1 Billion so it didn’t reach the target, there were muzakki who say the online zakat payment system in Dompet Dhuafa Waspada feels it has not been too well run.The response of the community that is still lacking because most of the loyal muzakki in Dompet Dhuafa Waspada is the elderly who are laymen to social media so that they prefer to pay their zakat through zakat pick-up services or cash zakat and less millennial that aware of the obligation to pay zakat. Keywords: Dompet Dhuafa Waspada; Payment of Zakat; Online Zakat payments.